TERMINAL BOARS AND OTHER MALE PARENTS IN HYBRIDIZATION SYSTEM - Berezovskyy, M. D.; Narizhna, O. L.; Vashchenko, P. A.; Shostya, A. M.; Usenko, S. O.; Kuzmenko, L. M.; Slynko, V. H. (Scientific Progress & Innovations, 2021)
The results of evaluation of fattening and meat qualities of hybrid young animals received from the com-bination of purebred and crossbred sows with terminal boars of the own reproduction on a farm in compari-son with other male parents – Landrace (L) and Pietren (P) breeds are highlighted. The main purpose of the work is to compare the terminal boars (T), created by using genotypes with purebred boars of Landrace and Pietren breeds and the control group of Large White (LW) × LW. The work was conducted on the farm of “Sviato-Nikolske” of Krynychanskyi district, Dnipropetrovsk region. Seven experimental groups were formed for the studies (LW – the Large White breed, L – Landrace breed, P – Pietren, T – terminal boars); І - ♀ LW × ♂LW, ІІ - ♀LW × ♂L, ІІІ - (♀LW × ♂L) × ♂L, IV - ♀LW × ♂P, V - ♀ (♀LW × ♂L) ×♂ P, VI - ♀LW × ♂Т, VII - ♀ (♀LW × ♂L ) × ♂T. According to the main indexes of fattening qualities, the following indicators were received: by the age of reaching the weight of 100 kg, groups V and VII had a significant advantage over group I (by 5.93–6.00 %, p≤0.001); by the average daily weight gain – groups II, V, VI and VII (by 8.97; 5.45; 7.50; 8.09 %, respectively, p≤0.001); by feed consumption – groups II and VII (by 5.4 %, at p≤0.001). According to the results of index assessment (fattening qualities), group I (♀LW × ♂LW) was behind all other groups in the range from 5.24 to 15.56 units. According to this index, groups II and VII are distinguished (10.48 and 15.56 units). The complex index demonstrates significant advantages of the above mentioned groups over the purebred group – from 14.26 to 28.14 units. Back-fat thickness has a great im-pact on the value of this index, which should be taken into account when selecting male parents in the hy-bridization system. Within each experimental group, the level of variability was determined (Cv max = 6.48), which indicates a high level of productive traits’ selection. This index was slightly higher by back- fat thick-ness (Cv max = 10.1). It has been established that genetic factor has a significant effect on fattening quali-ties, especially meat qualities (back-fat thickness). Therefore, this factor should be taken into account while choosing the scheme of crossing. As a result of studies, it has been established that the terminal boars of own reproduction demonstrated better results than purebred male parents and can be effectively used in the hybridization system.